Geographical Zones of Varanasi City: Past to Present - Jha, Darshan Kumar; Harshwardhan, Rahul; Tripathi, V.K. (National Geographical Journal of India, 2022)
Geography is a spatial science which investigates every process, phenomena and problem in a space with reference to time. To analyse different phenomena and of course their interaction geographically, it is essential to demarcate geographical zones of the city. In an urban centre, the processes, phenomena and its outcome can be best studied by delineating the geographical zones. The aim of this paper is to review the previous attempts of delineation, basis of delineation and demarcate the geographical zones of present Varanasi city with future prediction. The present city has been divided into three distinct geographical zones based on differences in street layout, land use, pattern of settlement and morphology of the city. The paper reveals that the city's geographical zones are continuously expanding and this expansion follows the concentric zone model in general but some new nuclei are also developing.